Using Exposure-Generalization-Reinforcement-Application (EGRA) Process Approach to Improve Students’ Writing Achievement - Ranti Pratiwi; Patuan Raja,; Flora (LPPM Universitas Advent Indonesia, 2026)
This study primarily examines students’ descriptive writing achievement using the combination of the Process Approach with the EGRA technique, as well as its impact on their writing improvement. Considering the limitations highlighted in earlier Process Approach studies, this research examines the extent to which integrating EGRA into the planning stage can offer a more effective solution to these limitations. A pretest-posttest experimental and control group design was used to collect quantitative data from senior high school students. A comparison was made between students instructed using the Process Approach combined with EGRA and those following the original Process Approach. The findings showed that the experimental group produced significantly better descriptive writing texts than the control group. Thus, combining the Process Approach with EGRA can offer an effective teaching strategy for enhancing students’ writing skills.